Investment in customer recognition and information exchange - Oz Shy; Rune Stenbacka (Federal Reserve Bank of Boston, 2012)
We investigate how costly acquisition and exchange of customer-specific information affects industry profit and consumer welfare. Consumers differ in their preferences for competing brands and in their switching costs between brands. Brand-producing firms use their acquired knowledge of customer-specific preferences to differentiate prices. We show that consumers are worse off when firms acquire information about their preferences and that information sharing between firms further magnifies their losses. No information sharing supports a subgame perfect equilibrium that is also efficient. Finally, equilibrium investments in customer information may be excessive if firms bear low costs of acquiring customer-specific information.
Keywords: D4; D82; L1; L4; 330; customer recognition; preference recognition; price discrimination; exchange of information; switching costs